Perbedaan Intoleransi Politik Jamaah Nahdlatul Wathan Terhadap Jamaah Ahmadiyah Ditinjau Dari Gender - Tutut Chusniyah; Fattah hidayat; Maulanal Kirom Firdaus (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
Political intolerance in this study is the unwillingness of a person or group to accept the actions, talks and views of the Ahmadiyya congregation which include disrespecting the civil rights of others, disrespecting freedom of expression, and disrespecting the beliefs of others. Gender roles are roles played by women and men in accordance with the status of the environment, culture and society structure. The aim of research to find out the differences of political intolerance in the congregation of the Ahmadiyya Muslim Nahdlatul Wathan Pancor, Lombok if the terms of gender. This study has 1 dependent variable, namely political intolerance with 1 independent variable, namely gender. The subjects of this study were 90 members of the Nahdlatul Wathan Jamaah, consisting of 45 men and 45 women. The research instrument used was the political intolerance scale (α = 0.837). The results showed that there was no difference in political intolerance between male and female Nahdlatul Wathan congregations against the Pancor Ahmadiyah Community, East Lombok with t count <t table (-0.362 <1.987) and P value (0.718> 0.05). Recommendations for future research to examine other variables that influence political intolerance, such as authoritarian variables, contacts or relationships, education, government policies and ethnic diversity.